Long-term remission with rituximab in refractory leucine-rich glioma inactivated 1 antibody encephalitis - Brown, J. William L.; Martin, Peter J.; Thorpe, John W.; Michell, Andrew W.; Coles, Alasdair J.; Cox, Amanda L.; Vincent, Angela; Zandi, Michael S. (Journal of neuroimmunology, 2014)
Autoimmune encephalitis associated with antibodies to leucine-rich glioma inactivated 1 (LGI1) is recently described and there is a lack of detailed reports on the treatment of relapsing or refractory cases and long-term outcomes. Two case reports are presented. Both cases had faciobrachial dystonic seizures (FBDS) and received rituximab after relapsing or refractory disease. Both cases achieved sustained clinical remission of up to 15 and 56months respectively. Rituximab use allowed withdrawal of corticosteroids and was well tolerated. Randomized clinical trials are needed in LGI1 encephalitis and other autoimmune encephalitides.